Measure of high frequency input impedance to study the instability of power devices in short circuit. (September 2018) - Abbate, C.; Busatto, G.; Sanseverino, A.; Tedesco, D.; Velardi, F.
Abstract: In this paper, we use a pulsed technique for measuring the input impedance of power devices when they are operated in real operating conditions like short circuit for identifying the situations for which these devices can become instable. The measurement results are used to study the stability in SC of several devices like IGBTs, Power MOSFETs in Si and in SiC, GaN power HEMTs. It is demonstrated that the proposed approach can be a very useful tool for designing the external circuit, and in particular the driver, in such a way to prevent the SC instabilities of power devices.